Currents shaped the genetic structure of Tridentiger barbatus (Günther 1861) along the Chinese coast - Wei, Jiehong; Liu, Min-Yun; Shiao, Jen-Chieh; Li, Fan; Yang, Jinquan; Iizuka, Yoshiyuki; Kang, Bin; Tseng, Ruo-Shan; Shao, Huan-Jie; Liao, Te-Yu (Frontiers in Marine Science, 2022)
The modern coast of China was characterized by complicated hydrology, which might be a potential factor to shape genetic structure of marine organisms. Tridentiger barbatus is a widespread benthic goby in coastal China, whose range expansion might depend on larval dispersal in its spawning season. We explored the genetic structure of T. barbatus and its interrelationships with coastal currents, planktonic larval duration and the Pleistocene climate fluctuations. Genealogies of cytb, Rh and RAG1 reveals two lineages in T. barbatus, namely the southern and northern lineages. The southern lineage distributes through the South China Sea to the South Yellow Sea but is absent from the North Yellow Sea and Bohai Sea. The HYCOM average flow field indicates an eddy between the North and South Yellow Sea, which might cause larval retention and limit dispersal of the southern lineage into the North Yellow Sea and the Bohai Sea. The northern lineage distributes through the South Yellow Sea to the Bohai Sea but is absent from the South China Sea and East China Sea. The distribution of the northern lineage fits the eastward deflection of the Yellow Sea Coastal Current at the boundary of the East China Sea and South Yellow Sea, which might limit southward larval dispersal of the northern lineage into the East China Sea. We also uncovered two cytb haplotype groups within the southern lineage, namely group A and B, whose distributions might be shaped by the northward Taiwan Warm Current. The coincidence between the genetic structure of T. barbatus and the coastal currents and eddy strongly implies significant roles of larval dispersal and current transportation in shaping genetic structure of T. barbatus. In addition, significant isolation by distance is found in the southern lineage, which coincide with its short planktonic larval duration (20-30 days). The inference on divergence time suggests that the observed lineages and haplotype groups in T. barbatus are originated in the Pleistocene glaciations. Therefore, the coastal currents, planktonic larval duration and historical glacial isolation are proposed as important factors shaping the genetic structure of T. barbatus.